2006
DOI: 10.1097/01.qai.0000233311.28602.4d
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women With HIV Infection Can Expect Healthy Survival

Abstract: The median-term postpartum prognosis of HIV-infected pregnant women with access to HAART is good. Exposure to short-course ZDVm or START during pregnancy did not jeopardize their response to subsequent therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
2
26
0
2
Order By: Relevance
“…Similar findings have been reported elsewhere. 17 The most significant finding from this study was the low rate of HIV follow-up care after delivery. Only 37% of these women had two or more documented visits with an HIV provider in 1 year, which is less frequent than what is recommended as the standard of longitudinal care.…”
Section: Discussionmentioning
confidence: 74%
“…Similar findings have been reported elsewhere. 17 The most significant finding from this study was the low rate of HIV follow-up care after delivery. Only 37% of these women had two or more documented visits with an HIV provider in 1 year, which is less frequent than what is recommended as the standard of longitudinal care.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, other studies have assessed VL changes among HIV-infected women according to the continuation or discontinuation of ARVs after delivery (Cao et al 1997, Melvin et al 1997, Watts et al 2003, Martin et al 2006, Tungsiripat et al 2007. Some studies have suggested no change in VL PP, although others indicated VL increases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies evaluating changes in the plasma HIV RNA concentration [viral load (VL)], the CD4 + lymphocyte percentage (CD4%) or absolute CD4 + lymphocyte count, or the HIV clinical disease stage in the postpartum (PP) period among HIV-infected women continuing or discontinuing ARVs after pregnancy have shown conflicting results (Cao et al 1997, Melvin et al 1997, Watts et al 2003, Martin et al 2006, Tungsiripat et al 2007, Cavallo et al 2010. To avoid the effect of a higher volume of distribution on absolute CD4 + lymphocyte counts, the CD4% should be used for monitoring T lymphocytes during pregnancy and PP (Miotti et al 1992, Ekouevi et al 2007).…”
mentioning
confidence: 99%
“…These studies included women who received mono-or dual-NRTI therapy during pregnancy, 16 did not assess for non-HIV outcomes, 16,17 and had shorter study periods. 18 These studies showed that women discontinuing ART postpartum either had an increased risk of progression to ADE or death, 16 no difference in progression to ADE or death, 17 or increased risk of class B events.…”
Section: Discussionmentioning
confidence: 99%
“…These studies included women who received mono-or dual-NRTI therapy during pregnancy, 16 did not assess for non-HIV outcomes, 16,17 and had shorter study periods. 18 These studies showed that women discontinuing ART postpartum either had an increased risk of progression to ADE or death, 16 no difference in progression to ADE or death, 17 or increased risk of class B events. 18 HAART use in our cohort was similar to the use in another study in a resource-rich setting over comparable period of time 19 : PI-based HAART regimen use increased and NNRTIand NRTI-based HAART regimen use decreased during the study period.…”
Section: Discussionmentioning
confidence: 99%